Spain : memorandum of interview / at lunch to Mr. del Vayo - Citrine, Walter, 1887-1983
016b-0046-001 PRIVATE & CONFIDENTIAL. MEMORANDUM OF INTERVIEW. Date 13th October, 1937. Time to Reference WMC/FP/63 Present At lunch to Mr. del Vayo. SUBJECT. SPAIN. On Wednesday, 13th October, I went to a lunch in honour of Mr. del Vayo at the Spanish Embassy. Incidentally, I was rather surprised to find who were present. The company consisted of Mr. Attlee, Philip Baker, Commander Fletcher, Lord Listowel, Ellen Wilkinson, and Gollancz, the publisher, in addition to the Spanish Ambassador and his Assistant Oleveira. In a few minutes conversation which I had with Del Vayo, he mentioned to me that he had been at the Mineworkers' Federation to see Mr. Edwards. I knew of the arrangements for this interview, but did not know what it was about. Del Vayo subsequently told me that the interview was to secure the appointment of a delegation or commission by the Mineworkers' International. The purpose of this delegation was to go to Gijon, so that in the event of the city falling Franco would be restrained from excesses by the presence of such a delegation. I expressed approval of the idea but said I thought the delegation would be much stronger if it contained persons not connected with the Labour Movement, particularly some representatives of the English church or the legal profession, and a public man or so, these to be in addition to such representatives as the Miners appointed. Mr. del Vayo asked whether the Commission should not be an international one, and contain representatives from other countries. I agreed with this view too. I suggested that Attlee's views should be obtained, and I found that he agreed with this general outline. I understood that the Spanish Ambassador was going to take the matter up to see whether such a Commission could be established, as del Vayo was leaving for Paris that night. 292/946/16b/50